Challenges in diagnosis and management in elderly presenting with very late-onset psychiatric symptoms and N-methyl-D-aspartate receptor autoimmune encephalitis - Anirban Dutta; Abhishek Ramesh; Harkishan Mamtani; Sandhya Mangalore; Shyam Sundar Arumugham; M Netravathi; Palanimuthu Thangaraju Sivakumar (Journal of Geriatric Mental Health)
N-methyl-D-aspartate receptor (NMDAR) encephalitis presents with psychiatric and neurological symptoms at various stages of the disease course. We present the case of a 70-year-old elderly woman with hypertension, diabetes mellitus, and a family history of psychotic disorder in her son with an illness of 8-year duration having initial episodes characterized by delusions of persecution, reference, auditory and visual hallucinations, aggression with subsequent episodes having additional features of suicidal ideations, and decreased food intake along with sensitivity to antipsychotics. The presence of fever, confusion, and faciobrachial movements in later course of illness revealed NMDAR positivity on further investigations and required continued care with immunomodulation, antipsychotics, and Electroconvulsive therapy. Affordability and poor compliance posed as serious challenges in the entire treatment process. Thus, the presentation of behavioral abnormalities in the elderly should be carefully evaluated and followed over time with due consideration given to atypical symptoms for alternate causes.